Gender-based comparative analysis of pre-service teachers’ mathematics performance at the Colleges of Education in Ghana - Brantuo, William Agyei; Klu, Theophilus Kwasi; Maanu, Vivian; Atta, Seth Amoako (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2024)
The study sought to find out the difference in mathematics achievement between males and females at the Presbyterian College of Education. The study employed the use of secondary data, that is, students' WASSCE entry results against their Final GPA at the College of Education were used for the data analysis. The population of the study was all students of Akropong Presbyterian College of Education, who were admitted in 2015 and 2016 and completed all the required courses and examinations in 2018 and 2019 respectively with the Diploma in Basic Education awarded by the University of Cape Coast. The sample size was 1024 and this comprised all the past students of Akropong Presbyterian College of Education, Akropong Presbyterian who graduated with the Diploma in Basic Education from 2016 to 2019. The results of the analysis proved that males entered with slightly better results than their female counterparts and the final GPA was in the same manner. The researcher therefore recommends that the college must move beyond the normal training and put in measures to ensure that most of the students can improve their performance to be at par with the current demands of a world-class teacher. More importantly, there should be enough gender-sensitive and female- friendly measures to ensure that the females catch up with the males in terms of academic achievement.